Natal’ya Vladimirovna Ryazantseva - Editorial Article (Бюллетень сибирской медицины, 2008)
Creative biography of professor, Philosophy Doctor, chief of the fundamental bases of clinical medicine chair, pro-rector on strategic devel opment and innovation policy of the Siberian State Medical University (Tomsk) N.V. Ryazantseva is presented in the article.